URGENSI SIDANG TIM PENGAMAT PEMASYARAKATAN (TPP) DALAM PEMENUHAN HAK-HAK NARAPIDANA DI LEMBAGA PEMASYARAKATAN NARKOTIKA KELAS IIA BANGLI - Anak Agung Gd Agung Kresna Astina; I Wayan Gde Wiryawan; Lis Julianti (Jurnal Yusthima, 2026)
The new paradigm of correctional system is the transformation from a prison system to a correctional system. One effort to avoid arbitrary behavior and subjective assessments in the implementation of training, then every decision to be given to individual inmates must be approved and approved through the Correctional Observation Team (TPP) Session. Although the legal framework has clearly established the TPP Session as a standard procedure, in operational practice there are still strong indications of procedural discrepancies. The research method used in this study is an empirical legal research method with qualitative research characteristics and analytical descriptive specifications. Data were collected through interviews, literature, and documentation. The collected data were analyzed using qualitative analysis methods. The results of the discussion obtained indicate that the Implementation of the TPP Session at the Class IIA Bangli Narcotics Prison prioritizes the principles of objectivity, transparency, and accountability. The TPP Session is held for the process of coaching and determining sanctions for violations. In its implementation, the presence of inmates in the session uses a representative system for training, while for violation cases it is mandatory to be included in the TPP session. The urgency of ensuring the rights of inmates through the implementation of TPP hearings is to fulfill human rights indicators, including 1) Procedural Justice & Non-Discrimination, 2) Rights to Self-Development & Rehabilitation, 3) Rights to be Heard and Accountable, 4) Rights to Health and Humane Treatment. Obstacles encountered in providing inmates' rights through TPP hearings include, first, overcapacity and second, inadequate human resources with assessment competencies. Efforts are being made to overcome these obstacles through employee competency in the TPP hearing mechanism to ensure the proper fulfillment of inmates' human rights.